Interbank exposures: an empirical examination of systemic risk in the Belgian banking system - Hans Degryse; Grégory Nguyen (National Bank of Belgium, 2004)
Robust (cross-border) interbank markets are important for the well functioning of modern financial systems. Yet, a network of interbank exposures may lead to domino effects following the event of an initial bank failure. The structure of the interbank market is a potential important driving factor in the risk and impact of interbank contagion. We investigate the evolution of contagion risk for the Belgian banking system over the period 1993-2002 using detailed information on aggregate interbank exposures of individual banks and on large bilateral interbank exposures. We find that a change from a complete structure (where all banks have symmetric links) towards a multiple money centre structure (where the money centres are symmetrically linked to some banks, which are themselves not linked together) as well as a more concentrated banking market have decreased the risk and impact of contagion. Moreover, an increase in the proportion of cross-border interbank assets has lowered the risk and impact of local contagion. Yet, this reduction was probably accompanied by an increase in contagion risk generated by foreign banks, although even here the contagion risk appears fairly limited.
Keywords: G20; G15; 330; Interbank markets; financial stability; financial integration; contagion; Geldmarkt; Schock; Finanzsektor; Bankenliquidität; Spillover-Effekt; Belgien